Microorganisms causing urinary tract infections in a teaching hospital in northeastern Brazil - Tuyanne Alves Chaves; Cecília Brenda Rocha Carneiro; Michael Peters; Carlos Ney Alencar de Araújo; Paula Karinny Mariano de Alencar; Antonio Junior de Lima Ferreira; Yasmine Carneiro Garcia; Paulo Jean do Nascimento Ferreira; Francisca Adilfa de Oliveira Garcia (Journal Health NPEPS, 2018)
ABSTRACT Objective: to study the UTI-causing bacteria frequency and sensitivity profiles in a teaching hospital in northeastern Brazil. Method: A retrospective cross-sectional study was conducted based on the review of 279 patients for whom uroculture and urinary catheter cultures were routinely processed in the Microbiology Laboratory of São Vicente de Paulo Hospital. Results: For the catheter culture group, the most frequent microorganism was Staphylococcus epidermidis (47%), while in urine culture group Escherichia coli was the microorganism most frequently isolated (52%). E. coli showed 76.46%, 70%, and 86.36% resistance to ampicillin, amoxicillin and Sulfamethoxazole/trimethoprim respectively. S. epidermidis showed high resistance to most drugs used, demonstrating that these drugs should not be used to treat UTIs in this institution. Conclusion: This study represents the first study evaluating bacterial resistance in this institution and since data involving epidemiological surveillance and microbiological are limited in this region and due to its importance in the national context, the results may reflect important information to the body of research/data on bacterial resistance in the world. RESUMO Objetivo: estudar os perfis de frequência e sensibilidade das bactérias causadoras de ITUs em um hospital universitário do nordeste brasileiro. Método: Foi realizado um estudo retrospectivo de corte transversal, com base na revisão de 279 pacientes, para os quais as culturas de urocultura e cateter urinário foram analisadas no Laboratório de Microbiologia do Hospital São Vicente de Paulo. Resultados: no grupo de cultura de cateteres, o microrganismo mais frequente foi o Staphylococcus epidermidis (47%), enquanto no grupo da urocultura a Escherichia coli foi o microrganismo mais isolado (52%). A E. coli mostrou 76,46%, 70% e 86,36% de resistência à ampicilina, amoxicilina e sulfametoxazol/trimetoprima, respectivamente. S. epidermidis mostrou uma alta resistência à maioria dos fármacos utilizados indicando que os medicamentos em questão não devem ser usados no tratamento de ITUs nessa instituição. Conclusão: Este estudo representa o primeiro estudo que avalia a resistência bacteriana nessa instituição e uma vez que os dados que envolvem vigilância epidemiológica e microbiológica são limitados nesta região e devido a sua importância no contexto nacional, estes resultados podem refletir informações importantes para o corpo de pesquisa/dados sobre resistência no mundo.